Pengaruh Efektivitas Penerapan Standar Akuntansi Pemerintahan Dan Kompetensi SDM Terhadap Kualitas Laporan Keuangan Pemerintahan Kabupaten Madiun - Verlina Dwi Rahayu; Khusnatul Zulfa; Iin Wijayanti (ITB AAS INDONESIA, 2023)
This research analyzes the impact of Government Accounting Standards implementation and Human Resources Competence on the financial report quality of the Madiun Regency government. High-quality financial information is essential for transparent decision-making in the governmental context. Multiple linear regression analysis is used to test hypotheses and create a predictive model. Data from the Madiun Regency government's financial reports over the last five years, as well as information on Government Accounting Standards implementation and Human Resources competence, were collected. The findings reveal that effective Government Accounting Standards implementation significantly influences financial report quality. Likewise, competent Human Resources play a crucial role in presenting accurate financial information and minimizing accounting errors. This study suggests that by enhancing the effectiveness of Government Accounting Standards and improving Human Resources competence, the Madiun Regency government can produce higher-quality financial reports, fostering accountability, transparency, and public trust in its financial performance.